Change of the precision of hand movements in young men after short-term (anaerobic) exercise - Dawid Koźlenia; Iwona Wierzbicka-Damska; Izabela Trojanowska; Jarosław Domaradzki (Kazimierz Wielki University, 2018)
Background: Physical exercise causes disturbances of body homoeostasis resulting in fatigue. This affect the quality of motor activity, including precision of hand movement. The objective of the work was to evaluate the effect of a short-term (anaerobic) physical exercise on hand movement in men in static and dynamic conditions. Materials &methods: The study group comprised of 52 young men aged 20.44±7.87 years old. Heartbeat frequency, systolic and diastolic blood pressure were measured. Precision of hand movement was studied with the use of the MLS module from the Vienna Test System. Tests of precise hand movements were conduced in static and dynamic conditions. A number of errors committed was analysed. Tests were performed with a dominant hand, twice: before and after an anaerobic exercise. The exercise test was to perform a maximum number of arm flexes in frontal support (press-ups), until denied. Results: Comparison of test results before and after the exercise indicated a statistically significant increase of hand tremor in statics and no changes in dynamics after the exercise. This occurrence was manifested by a number of errors made. Using multiple regression, it was shown that hand tremor in statics is related to body built. Higher values of height and body mass correlated with a greater number of errors. A statistically significant impact of resting heartbeat frequency on a number of errors in statics was also observed. In dynamic conditions, a relationship between hand tremor and a volume of work performed and the resultant heartbeat frequency was detected. The increase in number of flexes by one causes the increase in number of errors by two. Conclusion: Physical exercise significantly affects hand precision in statics in the students studied. Impact of physical exercise on a greater number of errors committed in a dynamic test was not observed.